2011
DOI: 10.1007/s00894-011-1312-0
|View full text |Cite
|
Sign up to set email alerts
|

On the potential application of DFT methods in predicting the interaction-induced electric properties of molecular complexes. Molecular H-bonded chains as a case of study

Abstract: A detailed analysis of the selected DFT functionals for the calculations of interaction-induced dipole moment, polarizability and first-order hyperpolarizability has been carried out. The hydrogen-bonded model chains consisting of HF, H2CO and H3N molecules have been chosen as a case study. The calculations of the components of the static electric properties using the diffuse Dunning’s basis set (aug-cc-pVDZ) have been performed employing different types of density functionals (B3LYP, LC-BLYP, PBE0, M06-2X and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…From these results, structures of precursors, intermediates, and scans for associated transition states were explored by using the PM3 semi-empirical algorithm 41 , both in Spartan 42 , for Linux v. Two (Wave function, Inc.). DFT (Density Functional Theory, part of Gaussian 03 and 09 suites, Gaussian Inc.) calculations were performed by using the PBE0 functional 43, 44 (PBE1PBE in Gaussian parlance) with basis sets Def2-SVP and Def2-TZVP 45 . Minima and transition states were optimized at the level PBE1PBE/Def2-SVP and confirmed by vibrational frequency analysis.…”
Section: Methodsmentioning
confidence: 99%
“…From these results, structures of precursors, intermediates, and scans for associated transition states were explored by using the PM3 semi-empirical algorithm 41 , both in Spartan 42 , for Linux v. Two (Wave function, Inc.). DFT (Density Functional Theory, part of Gaussian 03 and 09 suites, Gaussian Inc.) calculations were performed by using the PBE0 functional 43, 44 (PBE1PBE in Gaussian parlance) with basis sets Def2-SVP and Def2-TZVP 45 . Minima and transition states were optimized at the level PBE1PBE/Def2-SVP and confirmed by vibrational frequency analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Zawada et al have reported on the results of calculations of interaction‐induced dipole moment, polarizability, and first hyperpolarizability of three complexes: HF(HF) n , H 3 N(HF) n , and H 2 CO(H 2 CO) n . [6] The authors used five exchange‐correlation functionals (B3LYP, LC‐BLYP, PBE0, M06‐2X, and CAM‐B3LYP) and medium‐sized basis set, namely Dunning's correlation‐consistent aug‐cc‐pVDZ basis set. As the conclusions reported by Zawada et al are also vital for this study, we shall follow them closely discussing the data reported in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to lower order methods, like those based on density functional theory (DFT), introduces a considerable deterioration in the results, even in conjunction with a possibly large basis set size. [5, 6] In our recent work, we have turned our attention to another solution to the problem of the high cost of interaction‐induced electric property investigations, namely the use of the property‐oriented basis sets. [3, 4] A number of such basis sets is reported in the literature and successfully used for isolated systems as well as complexes, see, for example, the works by Maroulis and coworkers,[7–15] and Rappoport and Furche.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate choice of the computational level to be used in theoretical calculations of intermolecular systems, mainly those which are weakly bound, is a theme widely discussed among the theoreticians [2,[54][55]. It is well known that the many-body perturbation theory and density functionals are among the most commonly used theoretical approaches in studies on electronic structure, but it remains inconclusive whether B3LYP or MP2 is the most suitable for use in research on intermolecular systems [48,43,[56][57].…”
Section: Theoretical Methods: Criteria Of Choice and Applicationmentioning
confidence: 99%